Avaliação de projetos de pesquisa e desenvolvimento considerando a incerteza do tempo - Thiago Augusto de Oliveira Silva (2009)
The development time is one of the key factors that contribute to the newproduct development success. In spite of that, the impact of the time uncertainty on the development has not been fully exploited, as far as decision supporting models to evaluate this kind of projects is concerned. In this context, the objective of the present paper is to evaluate the development process of new technologies under time uncertainty. We introduce a model which captures this source of uncertainty and develop an algorithm to evaluate projects that incorporate Monte Carlo simulationand Dynamic Programming. The novelty in our approach is to thoroughly blend the stochastic time with a formal approach to the problem, which preserves the Markov property. We base our model on the distinction between the decision epoch and the stochastic time. We discuss and illustrate the applicability of our model through empirical examples.